2010
DOI: 10.1253/circj.cj-09-0979
|View full text |Cite
|
Sign up to set email alerts
|

Cut-Offs for Screening Prolonged QT Intervals From Fridericia's Formula in Children and Adolescents

Abstract: Background:The corrected QT interval (QTc) according to Bazett's formula (QTc = QT/RR 1/2 ) has been used in clinical practice. Bazett's formula, however, overcorrects the QT interval at fast heart rates and undercorrects it at low heart rates. Guidelines and some investigators have recommended using Fridericia's formula (QTc = QT/RR 1/3 ) in these cases, especially in tachycardic subjects. The aim of the present study was to determine cutoffs for QTc suitable for screening pediatric subjects with prolonged QT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 10 publications
0
16
1
Order By: Relevance
“…Pediatric cardiologists who participated in the program used age-and sex-specific criteria using an exponential formula (QT/RR 0.31 ) 21 or Fridericia formula. 22 In the screening program, cardiologists use computer-based QTc values as a reference because all ECG machines used in Japan are generally equipped with a function for automated measurement of QT intervals. However, manual measurement using the tangent method is usually applied to obtain QT intervals in Japan.…”
Section: Diagnosis Of Lqts and Screening Of Qt Intervals In The Schoomentioning
confidence: 99%
“…Pediatric cardiologists who participated in the program used age-and sex-specific criteria using an exponential formula (QT/RR 0.31 ) 21 or Fridericia formula. 22 In the screening program, cardiologists use computer-based QTc values as a reference because all ECG machines used in Japan are generally equipped with a function for automated measurement of QT intervals. However, manual measurement using the tangent method is usually applied to obtain QT intervals in Japan.…”
Section: Diagnosis Of Lqts and Screening Of Qt Intervals In The Schoomentioning
confidence: 99%
“…As in adults, data generally indicate that <5% of children have a QTc interval >450 ms. 44,79,97 In addition, as noted above, studies of siblings of children with long QT syndrome found increased risk of cardiovascular events at QTc intervals of 460 to 500 ms, though reported cases of torsades de pointes in children prescribed methadone are rare. Given the potential for increased risk and the availability of alternative opioids, the panel suggests that clinicians apply similar QTc parameters for use of methadone in children as in adults, until more evidence is available.…”
Section: Baseline Electrocardiogramsmentioning
confidence: 90%
“…17 The QT interval was not analyzed in the present study. Instead, manually measured data from a prior study 18 were analyzed and the data are shown in Table S2. …”
Section: T-wave Amplitudementioning
confidence: 99%